Flyrock in surface mining–part 4. Adaptation of Gurney model to predict burden velocity, flyrock velocity, and explosive energy partitioning in bench - T. Szendrei; S. Tose (The Southern African Institute of Mining and Metallurgy, 2026)
The Gurney approach to explosive/inert material interaction was adapted to analyse the face velocity in bench blasting. The model is based on the blasthole diameter, rock and explosive density, burden, spacing, linear charge density, and the Gurney energy constant. It is validated by comparing its predictions with a set of 20 field measurements of face velocities reported by Chiappetta et al. (1983) in an iron ore mine. The Gurney model links the observed large scatter of measured face velocities to the variation of the Gurney energy constant. This in turn is linked to the variability of the gas pressure acting on the burden. These variable pressures are generated when detonation product gases migrate into the extensive and complex fracture network around and between in-row blastholes. The energy efficiency of burden movement can be derived from the model. It is shown that ~7% of the explosive’s chemical energy is available for gas expansion work on the burden; of this quantity, 36% is actually converted to burden kinetic energy. That is, less than 3% of chemical energy is ultimately expended in burden displacement and throw. The model further indicatesnthat the projection of high-velocity (say, 100 m/s) flyrock is possible only when the path of leastnresistance through the burden has an effective density far less than the host rock. An equationnis derived that identifies the combinations of burden and path density that may yield flyrock. These values are specific to a particular baseline blast design.